Ideology in Education: The Descriptive, Negative, and Positive Approach on the Example of Selected Views in Catholic and Critical Pedagogy - Kruszelnicki, Wojciech (Hybris, 2023)
The paper compares the interpretation of the concept of ideology within educational research undertaken by certain Catholic scholars, with the secular problematization of this concept on the grounds of both Polish and foreign educational studies. By using the example of selected theorists representing Catholic pedagogy, the author aims to demonstrate the shortcomings of the dogmatically Catholic rendering of the notion of ideology in education; this very rendering is said to have infested education and therefore it is valued strictly negatively and remains in opposition to philosophically grounded scholarship, including the more progressive Catholic interpretations of this concept. It is argued that in order to think of ideology in a modern and critical way, one cannot cling only to the dogmatic teachings of the Catholic Church and has to take into consideration not only the negative meaning of the term, but also its descriptive and pedagogically positive significance, much in the way it is done in the discourse of critical pedagogy.